Kajian Normatif Terhadap Dualisme Kewenangan Penyidikan Dan Penuntutan Tindak Pidana Korupsi Antara Kepolisian, Kejaksaan Dan Kpk - Ariyantoro, Erwin; , Hartanto, S.H., M.Hum (2016)
This study aims to determine the authority of law enforcement police, prosecutors and the Corruption Eradication Commission (KPK) in the investigation and prosecution of corruption, and knowing the mechanism of investigation and prosecution of Corruption conducted the police, judiciary and the Commission. The method used is normative. This type of data consists of primary data and secondary data. The data source consists of research literature and field research. Data collection techniques to study the documentation, literature and interviews, then analyzed qualitatively and presented descriptively. The results showed frequent occurrence of conflict and overlapping authority, it is because the Commission has a multi authority or specificity in accordance with Act No. 30 of 2002 on the Corruption Eradication Commission. The mechanism of investigation and prosecution of Corruption by police, prosecutors and the Commission that if the Commission is not conducting an investigation, while the case has been conducted investigation by police or prosecutors, the two institutions it shall notify the Corruption Eradication Commission no later than 14 (fourteen) working days after the date of commencement of the investigation. After the Commission began an investigation, the investigations conducted by the Police or the Attorney is stopped immediately and then taken over by the Commission to continue to coordinate with the police and the judiciary.